Rapid integrated assessment of food safety related to pork in Vietnam: A consumer perspective - Hung Nguyen-Viet; Luu Quoc Toan; Dang Xuan Sinh; Nguyen Tien Thanh; Pham Van Hung; Grace, Delia (Veterinary Public Health Centre for Asia Pacific, 2013)
In Vietnam, pork makes up 75% of meat consumed, with its production delivering substantial benefits to the smallholders who supply 84% of the market. However, pork contains high levels of pathogens, an issue of growing concern among the public, and policy makers alike. To respond to these concerns, we developed a rapid integrated assessment tool with partners to assess food safety and zoonosis related to pork value chain and tested it in different countries. This study presents the results of this rapid assessment of food safety and zoonosis from a consumer perspective and with analysis of biological samples. Focus Group Discussions (FGD) were conducted in Hung Yen and Nghe An provinces for regular pork consumers and pregnant women or mothers of young children. In each province, three districts were selected, and one commune selected per district. Six FGD of 7 persons, stratified by income, were conducted in each commune, giving a total of 36 FGD and 252 participants in two provinces. The FGDs focused on food safety (hazard and risk), nutrition, and social and gender determinants of health and nutrition. Eighty pork samples were also collected in two province to rapidly capture the quality of pork from slaughterhouse and market through the measurement Total bacterial count (TBC), coliform, Water Holding Capacity (WHC) and pH. Participants were housewifes who often buy food for their family and are in charge of cooking pork. Pork is the main meat eaten daily in both provinces, representing 50-60% of total ASF consumption. Meat was bough mainly from the informal market and quickly prepared, cooked and consumed. People had high trust in pork safety and quality and rarely attributed health issues to pork consumption. Raw pork is rarely eaten except for fermented pork (nemchua) which is occasionally consumed. The main concern was growth promoters, pork refresher (chemicals used to make not fresh pork appear fresh) as well as diseased pork. There was little knowledge of zoonoses. The pork portions perceived as rich in nutrients were used young children and special care was given to their preparation, such as cooking well or making into soup. The TCB in swab samples at slaughterhouse varied from 10,500 to 3,410,000 CFU/400cm2 and coliform from 20 to 1.1*104 MPN/400cm2 .Pork samples collected in the market had TCB varying from 4.3*104 to 3280*104 CFU/g and coliform 40 to 1.1*104 MPN/g Pork pH after 1, 4 and 6h after slaughtering was in the range of 6.07-7.00), 5.35-6.95 5.15-6.02 respectively. The drip loss test showed that the water loss was from 1.26 to 5.92% after 48h. In conclusion, this rapid assessment shows that meat is a main animal food source in Vietnam and women are responsible for buying and preparing pork. While the trust in pork quality was high, microbial and physio-chemical analyses suggest further studies to address consumers’ concern on chemical contamination.